The Role of Family in Building Religious Awareness in Elementary School Children - Abdurahman, Ayi; Saro'i, Mohammad; Asfahani, Asfahani; Pranajaya, Syatria Adymas; Djollong, Andi Fitriani (BASICA Journal of Arts and Science in Primary Education, 2024)
This research aims to explore the role of the family in forming religious awareness in elementary school children. In the complex context of modern life, the role of the family is crucial in guiding children to religious values and awareness. Qualitative research methods were used with data collection techniques through in-depth interviews with parents and children, participant observation in daily family interactions, as well as content analysis of religious documents and materials used at home. The research results show that family interactions, parental role models, a supportive family environment, and religious practices at home all contribute to forming a strong foundation for children's religious awareness. These findings strengthen theoretical studies of the role of the family in religious education and child development, and provide a valuable contribution to a deeper understanding of the key factors that influence this process. In conclusion, the role of the family has a significant impact in forming religious awareness in elementary school-aged children, and efforts need to continue to be made to strengthen the positive role of the family in children's religious education.